(untitled) (Práxis Educativa, 2024)
In Chile, with the Inclusion Law (2015), a new cycle of reforms began in the educational system that attempted to modify the role of the market. This article analyses the implementation of free access to subsidized private provision in 717 subsidized private schools in the Santiago Metropolitan Area. Using logistic regression models, it examines the factors that influence eliminating school fees and investigates their implications for educational policy. The results reveal that the effect of the free provision is concentrated in a specific segment of the provision where institutional and school characteristics significantly influence its adoption. However, its effects are not stable over time, except for the collection from families, which remains significant. Keywords: School Fees. Gratuity. Mixed provision. Equity. Inclusion.